Infectious. - Bowden, Frank (University of New South Wales Press, 2016)
A woman's innocuous cold symptoms mask a debilitating rare tick infection. A young man develops shingles, then suffers blinding head pain later in life. After years of frustration, a family eradicates head lice forever. Leading infectious diseases specialist Frank Bowden sheds light the everyday illnesses that affect most of us (colds, sore throats), and the more serious issues that keep us awake at night (antibiotic resistance, Ebola). He busts myths, explores symptoms, treatments and covers the latest medical breakthroughs, and the big issues affecting public health. Bowden offers eye-opening insights into infectious diseases from a doctor's perspective, doled out with honesty, empathy and a dose of humor.